Synthesis and development of polymers-infiltrated porous iron for temporary medical implants: a preliminary result - Yusop, A. H. (2013)
Iron has been viewed as a promised biodegradable metal for temporary implants but its slow degradation is considered as the main limitation. Some works have been done to improve its degradation rate including by alloying and by processing through powder metallurgy. This work presents new approach to accelerate the degradation rate of iron by infiltrating biodegradable polymer into the pores of bulk iron foam. Solution of poly(L-lactic-co-glycolic acid) or PLGA was infiltrated into the iron foam by vacuum infiltration method to form PLGA-infiltrated porous iron (PIPI). It was found that the existence of PLGA in the iron foam maintained the mechanical property as that of iron foam. Degradation test has shown that the PLGA lead the degradation in PIPI samples. This preliminary work has shown the potentiality of the incorporation of biodegradable polymers into biodegradable metals for tailoring their degradation rate.